Effect of work and diet on body weight change, body condition and lactation performance of F1 crossbred cows used for draught - Gemeda, T.; Zerbini, E.; Gebre-Wold, A.; Demissie, D. (Ethiopian Society of Animal Production, 1995)
Forty pregnant F1 crossbred dairy cows (20 Friesian x Boran and 20 Simmental x Boran) were stratified in a 2 x 2 Diet x Work factorial experiment (not working, not supplemented; not working, supplemented; working, not supplemented; and working, supplemented). Working cows pulled sledges 100 days/yr (pull=350 to 450 N, 4 h/day, 4 days/week). Work output of supplemented and non supplemented cows was similar over one and two years. Over all three years, dry matter intake (g/kg 75) was greater for working compared to non working cows. Body weight changes and body condition score were similar for working and non working cows. Non supplemented cows lost weight throughout the first two years period, while supplemented cows tended to maintain or gain body weight over one and three years. Over two years, supplementation of working cows reduced live weight loss by 73 percent and doubled the number of conceptions and parturitions. Days in milk, milk, milk fat and protein yields were similar for working and non working cows, but were greater for supplemented compared to non supplemented cows. Total conceptions and calves born in all three years tended to be greater for supplemented and non working compared to non supplemented and working cows. These results indicate the potential of on-farm adoption of a cow traction technology that includes improved feed production and feeding strategies.